Paris 1944 : occupation, resistance, liberation - Bishop, Patrick (Patrick Joseph) (Pegasus Books, 2024)
A social history of the liberation of Paris from the German occupation during World War II. This account provides perspectives from both sides of the conflict, including French, German, and American participants